Self -service car washer and vehicle washing system - MA CHENGLING; PANG HONG; QUAN JUNMIN (2018)
The utility model provides a pair of self -service car washer and vehicle washing system relates to carwash technical field, including central controller, detecting element and steam unit, detecting element for detect current vehicle and whether be the reservation vehicle, and generate control signal according to the testing result, central controller is connected with detecting element and steamunit electricity respectively for acquire control signal, and opening or closing according to control signal control steam unit. In above -mentioned technical scheme, self -service car washer can realize making an appointment automatic carwash, after the car owner realizes having made an appointment the carwash, as agreed the time automatic car washer goes to, the carwash region of automatic car washer is reachd when the vehicle and after, detecting element can detect the vehicle that drives in the carwash present into regional, after having confirmed that current vehicle is for the reservation vehicle, just can open